Constructing flavour perception: from destruction to creation and back again. Issue 1 (December 2016) - Spence, Charles; Youssef, Jozef
Abstract We review the evidence suggesting that the bistable/multistable percepts that exist in the so-called higher senses of vision, audition, and touch do not seem to occur in the chemical senses (e.g. taste, aroma, and flavour). While we can undoubtedly be mistaken about our interpretation of chemical stimuli and while certain aromas/flavours do support multiple 'correct' interpretations, the perceptual switches occur only rarely rather than repeatedly. In fact, the interpretational changes that chemical stimuli occasionally undergo seem to have more in common with the phenomenon of the Gestalt principle of 'emergence' than with multistable perception. We highlight a number of potential differences in information-processing/attention between the senses that may underpin such perceptual differences. Finally, we describe a new dish created by chef Jozef Youssef in order to illustrate the concept of emergence and support discussion of the theme of gastronomy, just like art, as a matter of interpretation. The Picasso dish was served recently at the Gastrophysics dining concept delivered by Kitchen Theory in London.